Alternative approaches to game scheduling of multiple round-robin tournament: Korea professional soccer league (K League 1) in focus - Ko, Dae-Gon; Kim, Ha-Ram; Kim, Tae-Ho (Edelweiss Applied Science and Technology, 2025)
This study evaluates the quality of the current schedule of a professional soccer league, K League 1 (Korea Professional Soccer League), which is regarded as the top Asian professional soccer league and has unique characteristics compared to European leagues, such as odd numbers of games between some teams and final rounds based on previous performance. It assesses the total travel distance of teams to play all scheduled games, match fairness, and attendance fairness. Match fairness implies that each team should have the opportunity to play against other teams under similar performance conditions. Teams can be under different performance conditions during a long season due to several reasons, such as injuries and the level of team spirit. Attendance fairness relates to the maximum number of consecutive home or away series for each team. Alternatives that prioritize the minimization of the total travel distance while satisfying other factors are presented. The requirements of soccer league game scheduling differ in certain aspects from those of other sports leagues, like baseball leagues. Moreover, minimization results are compared with the 2023 K League 1 schedule and schedules generated by tournament scheduling methods, including the English Tournament Scheduling approach, where teams face previous opponents in reverse order. Despite extensive research, this study develops a new integer programming model and applies an existing heuristic to K League 1. Using quantitative methods, our research demonstrates match generation and adjustment issues, highlighting significant room for improvement in soccer scheduling.